English English - Isnaini, Linda; Trisanti, Novia ((JIBS) JURNAL ILMIAH BAHASA DAN SASTRA, 2025)
Current educational trends emphasize the increasing focus on teachers' strategies for questioning to enhance student engagement in the classroom. Despite the growing recognition of these practices as effective techniques for active learning, there is a lack of research investigating how teachers' questioning strategies affect how students engage. This study aimed to investigate how the questioning strategies influence students' engagement during classroom interaction. The research employed a qualitative case study analyzing the teacher’s questioning strategies and students' engagement during the classroom instructional process and the teacher’s interview. The participants were an English teacher and a vocational high school class in Semarang, Central Java, Indonesia. The study revealed that the teacher used five types of teacher’s questioning strategies proposed by Chen (2016): wait time, probing, repetition, paraphrasing, and simplifying. Among the most frequently used were wait times and probing types of strategies. In addition, the strategies in question affect the students' engagement; for example, waiting time encourages behavioral and cognitive engagement, probing increases cognitive engagement, and simplistic and repetitive language use increases affective and behavioral engagement. These results emphasized the need for teacher questioning to engage students in classroom activities. Therefore, by understanding how the teacher’s questioning affects the students' engagement, the teacher could improve their questioning strategies skills to engage students and encourage active participation in classroom interaction.